Epidemiology and associated factors of genital warts among patients in Iran: A cross-sectional study highlighting the impact of education and sexual behavior - Hossein Faramarzi; Hasti Jofreyi; Nahid Heydari Marandi; Mehdi Ghahartars; Nasrin Aliabadi (Clinical Epidemiology and Global Health)
Background: Human papillomavirus (HPV) infection is more prevalent among people and their sexual partners. This study aims to assess the prevalence of genital warts, examine associated factors like education and sexual behavior, and identify key factors influencing their occurrence in Iran. Materials and methods: This cross-sectional study was conducted on all patients with genital warts who were examined in Shahid Faghihi Dermatology Consultation Unit, Shiraz, Iran and underwent an HIV test in 2018. The associated factors related to genital warts and HIV test (negative/positive) in patients were determined using univariate analyses in our study. The study considered findings with a p-value below 0.05 to be statistically significant. Results: Out of 679 participants in this study, 498(73.3 %) were male and 181(26.7 %) were females. The average age of participants was 32.1 ± 9.1 years. The frequency of higher education and permanent marriage were 329 (48.4 %) and 415 (61.1 %) individuals, respectively. Moreover, 98 (14.4 %) and participants who confirmed eGW suffer from addiction and 2 (0.3 %) from drug Injection. In addition, 528 (77.8 %) had unprotected sex, 298 (43.9 %) had multiple sexual partners, and 35 (5.1 %) participants had homosexual sex. In addition, the frequency of HIV positive in patients who suffer from genital warts was 3 (0.4 %). Conclusion: The findings of this study suggest a strong correlation between associated factors and eGW. Notably, individuals with higher education levels tend to experience a higher prevalence of genital warts. Furthermore, the findings showed that eGW was strongly linked to a past of engaging in sexual activity with multiple partners.